Pautas de respuesta biogeoquímica durante las crecidas en una cuenca de encinar - Avila A.; Rodá F. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
The stormflow solute behaviour of a stream draining an evergreen oak forested watershed was studied. The biogeochemical response depended strongly on the watershed antecedent conditions. Under dry antecedent conditions very few runoff was produced and dilution of lithologic components and HCO3 was small. Sulphate, Cl, NO3 and K increased the two latter sometimes dramatically. The overall response of stormflow under dry antecedent conditions indicates that Horton overland flow dominates the hydrograph. Under wet antecedent conditions higher runoff was produced and dilution of lithologic components and HCO3 was of more importance. Sulphate and Cl increased, but NO3 and K showed very small increases if any. This type of response agrees well with subsurface flow dominating the hydrograph. When considering the solute range of variation during stormflow, 5 types of response have been obtained.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)